Tradisi Fotu Nina Dalam Pembentukan Moral Keluarga ( Studi Tradisi Masyarakat Didesa Sisobawino II Kecamatan Lolofitu Moi Kabupaten Nias Barat) - Vinal Fornia Gulo; Besti Zebua; Ferti S Juwita Zai; Selmanto Gulo; Agnes Monica Waruwu; Kurniawan Aprilyadin Waruwu; Rintis Mei Ampuni Zebua; Rivaldo Sastriawan Gulo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Fotu Nina tradition is a noble cultural tradition of the Nias people that plays a crucial role in shaping family morals. As a form of moral education, Fotu Nina is advice or guidance imparted by parents or traditional leaders to their children, especially in important situations such as approaching marriage, migrating from one's home, or entering adulthood. This study aims to analyze the meaning and role of Fotu Nina in shaping the character and morals of children within Nias families. Using a qualitative approach through in-depth interviews and participant observation, this study found that the Fotu Nina tradition embodies values such as honesty, responsibility, respect for parents, hard work, and solidarity. These values are believed to have a significant impact on shaping the behavior and personality of children within the family. Despite facing challenges such as the influence of modern culture and limited interaction time between parents and children, Fotu Nina remains relevant as a model of character education based on local wisdom. This study suggests the importance of revitalizing the Fotu Nina tradition as part of character education in the era of globalization, so that it can continue to strengthen the morals of the younger generation and Nias families.